Penggunaan Multimedia Inshot Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Al-Qur’an Hadis - Maria, Anly; Nurahman, Muhamad Azis (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Student understanding is the ability to comprehend problems, interpret, and restate them in one's own words. In terms of understanding, students must master skills such as translating, connecting, and interpreting information. However, in reality, student understanding in the Al-Qur'an Hadith subject in Class XI MIPA at MA Al-Musaddadiyah Garut remains low. This is evidenced by findings showing that many students are unable to explain the material presented and cannot summarize the material using their own words. Observations of the daily test scores for the Al-Qur'an Hadith subject in Class XI MIPA reveal that 51% of students have not yet met the Minimum Mastery Criteria (KKM). This indicates that many students do not have a satisfactory level of understanding. To address this issue, one solution that can be employed is the use of instructional media. One form of educational media that is expected to enhance student understanding is the use of InShot multimedia. InShot multimedia is a combination of text, audio, images, animations, and videos edited using the InShot application and can be presented interactively. The purpose of this study is to describe the effect of using InShot multimedia on student understanding in the Al-Qur'an Hadith subject in Class XI MIPA. The research methodology employed is descriptive with the type of Classroom Action Research (CAR). The data sources utilized in this study include primary and secondary sources. Data collection techniques involve observation, interviews, and written tests. Data analysis techniques used in this research include planning, action, observation, and reflection. The results of this study indicate that the use of InShot multimedia can improve student understanding. This is demonstrated by the fulfillment of five indicators of student understanding, namely: the ability to interpret, provide examples, classify, draw inferences, and compare.  Keywords: InShot Multimedia, Student Understanding, Al-Qur'an Hadith Subject